(untitled) (ENTHYMEMA, 2024)
The article focuses on the space of the comic in Mimesis, an essay that sets its foundation on the serious, tragic and problematic treatment of the everyday. Placing Auerbach within his ideological horizon and briefly reconstructing his intellectual genealogy, the analysis interrogates the reasons that led the author to consider the comic as a "form" that avoids the emergence of realist complexity. After a discussion of two basic problems (one semiological, one historical), the article goes through Mimesis’s chapters in which Auerbach treats the comic – chapters that often turn out to be useful to understanding his method and world view.